Pelaksanaan Gadai Emas Dengan Sistem Syariah (Studi di Bank Syariah Mandiri Cabang Surakarta) - Doriy, Akun Gaura, Septarina Budiwati, S.H.,C.N.,M.H, Mutimatun Ni'ami, S.H.,M.Hum (2015)
The purpose of this study was to determine: (1) the implementation of gold pawn with sharia system; (2) the suitability of the system implementation gold pawn sharia Islamic law and the rules of Shari'ah principles of gold Rahn; (3) obstacles that arise in the implementation of the gold pawn with sharia system. This research includes empirical juridical ie an approach which refers to the rules written to then see how the implementation on the ground. The research was conducted at PT. Bank Syariah Mandiri Branch of Surakarta. Source of data using primary data from interviews, observation, and literature study. Data were analyzed using qualitative analysis. The results showed that: (1) The implementation of sharia gold pawn in Surakarta Branch BSM is using Rahn and Ijarah contract. Rahn contract is a contract granting a loan from the bank to the customer, along with assignments in order to keep the bank guarantee submitted goods, while the cost of maintenance using Ijarah contract; (2) Implementation of gold pawn with Shariah Islamic system in Bank Mandiri Branch Semarang Solo is in conformity with the rules of Islamic law and the principles of Shari'ah about Rahn gold, which is guided by the Sharia Board of the National Fatwa Council of Ulama Indonesia No: 26 / DSN-MUI / III / 2002 on gold Rahn; (3) Barriers arising in the implementation of the gold pawn with sharia system in Surakarta Branch Bank Syariah Mandiri, among others: a difference of opinion that the imposition of Islamic law with two contract transactions prohibited by the Prophet Muhammad, customers do not understand the mechanism of Rahn contract, customers who do not discipline pay installments, so that at maturity the pledged gold auctioned by the bank.